Enhancing Client Satisfaction: Utilizing Feedback for Ongoing Improvement Strategies - Ronald A Gonzales; Mary Rose Montano; Aveto M Dasal Jr; Renante A Artificio; Anna Rhea C Opeña; Maria Mylin S Miranda; Meljhon G Mosca; Armando A Salenga Jr (Research Synergy Foundation Press, 2025)
This study evaluated client satisfaction with the services provided by the City College of Calamba (CCC), with particular focus on the implementation of its Citizens' Charter and compliance with Republic Act No. 11032. Using a descriptive research design with 2,633 respondents, the study measured satisfaction across eight service quality dimensions, revealing an overall